DELIRIUM AFTER CORONARY ARTERY BYPASS GRAFT SURGERY AND LATE MORTALITY - Gottesman, R.F. (2010)
OBJECTIVES: Delirium is common after cardiac surgery, although underrecognized, and its long-term consequences are likely underestimated. The primary goal of this study was to determine whether patients with delirium after coronary artery bypass graft (CABG) surgery have higher long-term out-of-hospital mortality when compared to CABG patients without delirium. METHODS: We studied 5,034 consecutive patients undergoing CABG surgery at a single institution from 1997–2007. Presence or absence of neurologic complications, including delirium, was assessed prospectively. Survival analysis was performed to determine the role of delirium in the hazard of death, including a propensity score to adjust for potential confounders. These analyses were repeated to determine the association between postoperative stroke and long-term mortality. RESULTS: Individuals with delirium had an increased hazard of death (adjusted HR 1.65, 95% CI 1.38, 1.97), up to 10 years postoperatively, after adjustment for perioperative and vascular risk factors. Patients with postoperative stroke had a HR of 2.34 (95% CI 1.87–2.92). The effect of delirium on subsequent mortality was the strongest among those without a prior stroke (HR 1.83 vs HR 1.11 (with a prior stroke) (p-interaction=0.02) or who were younger (HR 2.42 (under 65 yo) vs HR 1.49 (65 yo and older) (p-interaction=0.04). INTERPRETATION: Delirium after cardiac surgery is a strong independent predictor of mortality up to 10 years postoperatively, especially in younger individuals and in those without prior stroke. Future studies are needed to determine the impact of delirium prevention and/or treatment in long-term patient mortality.